Studi Kesesuaian Wisata dan Mutu Air Laut untuk Ekowisata Rekreasi Pantai di Pantai Maron Kota Semarang - Fithor, Alin; Indarjo, Agus; Ario, Raden (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Semarang as nautical city has tourism recreation of them is Maron beach. The recent problem is, Maron beach has great potential in nautical tourism, while management have not done optimally. The developing of tourism in Semarang need to be implemented by developing design which is more emphasizes of quality than quantity to be based on the potential and growing problem. The purposes of the study are to determine assess the suitability of Land and Water Quality for Marine Ecotourism in Coastal Recreation Maron Semarang. Research conducted in April 2012-January 2013. The objective method used in this research is a case study conducted explorative. Analyzing data is used index conformity Tourism and Water Quality Standard Marine for Marine Tourism in appropriate with the Policy of the Minister of Environment Number 51 of 2004 as soon as Index Environmental Water Quality. The results show that the calculation of index suitability travel beach recreation activities is 66%. This indicates that the coastal Maron Beach Semarang classified in the category Match (S2). While the value of Index Environmental Water Quality as much as 31.1 for category as bad category.